2018
DOI: 10.3847/1538-4357/aaccf6
|View full text |Cite
|
Sign up to set email alerts
|

A Chandra/LETGS Survey of Main-sequence Stars

Abstract: We analyze the X-ray spectra of 19 main sequence stars observed by Chandra using its LETGS configuration. Emission measure (EM) distributions are computed based on emission line measurements, an analysis that also yields evaluations of coronal abundances. The use of newer atomic physics data results in significant changes compared to past published analyses. The stellar EM distributions correlate with surface X-ray flux (F X ) in a predictable way, regardless of spectral type. Thus, we provide EM distributions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 130 publications
(190 reference statements)
2
67
2
1
Order By: Relevance
“…In contrast, in very active stellar coronae the pattern is reversed into an "Inverse FIP Effect", with low FIP elements appearing underabundant relative to high FIP elements. These abundance fractionation patterns appear to be a function of both activity level and spectral type (see, e.g., Drake 2003; Robrade & Schmitt 2005;Laming 2015;Wood et al 2018). This is evidence that stellar CMEs could consist of plasma with different characteristics-both temperature and chemical composition-than the plasma in solar CMEs.…”
Section: Sources Of Error and Discrepancymentioning
confidence: 95%
“…In contrast, in very active stellar coronae the pattern is reversed into an "Inverse FIP Effect", with low FIP elements appearing underabundant relative to high FIP elements. These abundance fractionation patterns appear to be a function of both activity level and spectral type (see, e.g., Drake 2003; Robrade & Schmitt 2005;Laming 2015;Wood et al 2018). This is evidence that stellar CMEs could consist of plasma with different characteristics-both temperature and chemical composition-than the plasma in solar CMEs.…”
Section: Sources Of Error and Discrepancymentioning
confidence: 95%
“…Furthermore, for main-sequence stars in the unsaturated regime, we will assume a correlation between the X-ray flux and the coronal temperature in the closed loops such that (Preibisch 1997;Wood et al 2018)…”
Section: Coronal Temperature and Density: X-ray Luminosity Consistencymentioning
confidence: 99%
“…The robustness of the single temperature scaling hypothesis can nevertheless be questioned. In closed loops, available estimates of T l (Preibisch 1997; Wood et al 2018) fall back on an emission measure weighted average coronal temperature, based on heavy ions emission (Güdel 2007). From the wind model point of view, based on the modelling of a perfectly ionized hydrogen gas, the electron temperature (which is in this context similar to the proton temperature) is required to compute the mass-loss rate.…”
Section: Scenario 1: Single Temperature Scalingmentioning
confidence: 99%
“…The solar FIP effect decreases from G to early K-type stars and becomes zero at ∼ K5 then reverses to the IFIP effect for later K stars and M dwarfs. Wood et al (2018) extended the FIP biasspectral type relationship to include stars of earlier spectral types A and F. It is worth noting that the observed composition of stellar coronae can be more complex than having either a straightforward FIP or IFIP effect. For example, Peretz et al (2015) found that all elements were consistently depleted in the coronae of six main sequence stars of spectral type F7-K1 compared to their respective photospheres, whether compared to solar abundances or the individual stellar abundances.…”
Section: Introductionmentioning
confidence: 99%